Potential of Endogenous Oxytocin in Endocrine Treatment and Prevention of COVID-19 - Wang, Stephani C.; Zhang, Fengmin; Zhu, Hui; Yang, Haipeng; Liu, Yang; Wang, Ping; Parpura, Vladimir; Wang, Yu-Feng (Frontiers in Endocrinology, 2022)
Coronavirus disease 2019 or COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a significant threat to the health of human beings. While wearing mask, maintaining social distance and performing self-quarantine can reduce virus spreading passively, vaccination actively enhances immune defense against COVID-19. However, mutations of SARS-CoV-2 and presence of asymptomatic carriers frustrate the effort of completely conquering COVID-19. A strategy that can reduce the susceptibility and thus prevent COVID-19 while blocking viral invasion and pathogenesis independent of viral antigen stability is highly desirable. In the pathogenesis of COVID-19 disease, endocrine disorders have been implicated. Correspondingly, many hormones have been identified to possess therapeutic potential of treating COVID-19 diseases, such as estrogen, melatonin, corticosteroids, thyroid hormone and oxytocin. Among them, oxytocin has the potential of both treatment and prevention of COVID-19. This is based on its promotion of immune-metabolic homeostasis, suppression of inflammation and pre-existing comorbidities, acceleration of damage repair, and reduction of individuals’ susceptibility to pathogen infection. To COVID-19, oxytocin may specifically inactivate SARS-COV-2 spike protein and block viral entry into cells via angiotensin-converting enzyme 2 by suppressing serine protease and increasing interferon and T-lymphocytes. In addition, oxytocin can promote parasympathetic outflow and the secretion of body fluids that could dilute and even inactivate SARS-CoV-2 on the surface of cornea, oral cavity and gastrointestinal tract. What we need to do now is clinical trials. This trial should fully balance the advantages and disadvantages of oxytocin application, consider the time- and dose-dependency of oxytocin effects, optimize the dosage form and administration approach, combine oxytocin with inhibitors of SARS-CoV-2 replication, apply specific passive immunization, and timely utilize efficient vaccinates. Meanwhile, blocking COVID-19 transmission chain and developing other efficient anti-SARS-CoV-2 drugs are also important. In addition, relative to the complex issues with drug applications over a long term, oxytocin can be mobilized through many physiological stimuli, and thus used as a general prevention measure. In this review, we explore the potential of oxytocin for treatment and prevention of COVID-19 and perhaps other similar pathogens.